2021
DOI: 10.3390/ma14185338
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Ceramic Scaffolds for Bone Tissue Engineering by Powder Bed Selective Laser Processing: A Review

Abstract: The implementation of a powder bed selective laser processing (PBSLP) technique for bioactive ceramics, including selective laser sintering and melting (SLM/SLS), a laser powder bed fusion (L-PBF) approach is far more challenging when compared to its metallic and polymeric counterparts for the fabrication of biomedical materials. Direct PBSLP can offer binder-free fabrication of bioactive scaffolds without involving postprocessing techniques. This review explicitly focuses on the PBSLP technique for bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 180 publications
(252 reference statements)
0
36
0
Order By: Relevance
“…Calcium silicate bioceramics were also reviewed in a recent paper [34]. Both calcium phosphates and calcium silicates were used to fabricate porous ceramic scaffolds for tissue engineering [35]; it was also suggested that porous β-wollastonite has better bone regenerative potential compared to β-tricalcium phosphate scaffolds when implanted in vivo (rabbit calvarial defect model) [36].…”
Section: Resultsmentioning
confidence: 99%
“…Calcium silicate bioceramics were also reviewed in a recent paper [34]. Both calcium phosphates and calcium silicates were used to fabricate porous ceramic scaffolds for tissue engineering [35]; it was also suggested that porous β-wollastonite has better bone regenerative potential compared to β-tricalcium phosphate scaffolds when implanted in vivo (rabbit calvarial defect model) [36].…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Chemistry frontiersin.org (Kamboj et al, 2021), metals (Xia et al, 2023a), and their composites (Liu et al, 2022a) for bone tissue engineering.…”
Section: L-pbf As the Mainstream Manufacturing Technology For Am Mg A...mentioning
confidence: 99%
“…L-PBF is a laser AM technology based on the layered construction of complex customized implants using high-intensity laser beams. Therefore, it has been extensively investigated for the fabrication of bone implants using polymers ( Kamboj et al, 2021 ), metals ( Xia et al, 2023a ), and their composites ( Liu et al, 2022a ) for bone tissue engineering. L-PBF has shown excellent performance in customizing products with complex shapes.…”
Section: Am and Mg Alloys For Bone Repairmentioning
confidence: 99%
“…Cells, growth factors, and scaffolds are a necessary triad for tissue engineering. Despite advances in scaffold development and the identification of new growth factors and their genetic manipulation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], delivering sufficient numbers of cells and maintaining them in areas of interest, regardless of whether for ex vivo tissue engineering or in situ regeneration, has been challenging [ 1 , 12 , 15 , 16 , 17 , 18 , 19 , 20 ]. The effective delivery of stem cells or osteogenic cells derived from bone marrow or other source organs has been investigated in the context of tissue engineering and regeneration [ 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%